Pengaruh Lingkungan Kerja Dan Keselamatan Kerja Terhadap Resiko Kecelakaan Kerja Di Perusahaan Perkebunan Kelapa Sawit PT. Niagamas Gemilang Kabupaten Kutai Kartanegara - Sabran, Sabran; Fathurrahman, Achmad; Fahmi, Fahmi (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2021)
Abstract: The purpose of this study was to determine and analyze the influence of the Work Environment and Work Safety and to determine the most dominant variable influencing the Work Environment and Work Safety on the Risk of Accidents at the Oil Palm Plantation Company PT. Niagamas Gemilang, in Sungai Payang Village, Loa Kulu District, Kutai Kartanegara Regency. The analytical tool used is multiple linear regression with a sample of 91 people. The results showed that the variables of the Work Environment and Work Safety had a simultaneous effect on the Risk of Accidents at Work. Work Environment and Work Safety variables have a partial effect on the Risk of Work Accidents at PT. Brilliant Niagamas. Besides that, the work safety variable has a dominant effect on the risk of work accidents at PT. Brilliant Niagamas. Keywords: Work Accident and Occupational Safety, Risk of Work Accident